A Topical Treatment Optimization Programme (TTOP) improves clinical outcome for calcipotriol/betamethasone gel in psoriasis: results of a 64‐week multinational randomized phase IV study in 1790 patients (PSO‐TOP). (6th June 2017) - Reich, K.; Zschocke, I.; Bachelez, H.; de Jong, E.M.G.J.; Gisondi, P.; Puig, L.; Warren, R.B.; Ortland, C.; Mrowietz, U.; ,
Summary: Background: Around two‐thirds of patients with psoriasis do not adhere to topical treatment. The Topical Treatment Optimization Programme (TTOP), a five‐element tool, includes guidance for the conversation between dermatologists/nurses and patients, patient information material, telephone/e‐mail helpdesks and treatment reminders. It has been developed by patients and dermatologists to help increase adherence to treatment in psoriasis. Objectives: To compare TTOP with standard of care ('non‐TTOP') within a large European investigator‐initiated study, PSO‐TOP (clinicaltrials.gov NCT01587755). Methods: Patients with mild‐to‐moderate psoriasis received calcipotriol/betamethasone dipropionate gel as standardized study medication and were randomized 1 : 1 to either TTOP or non‐TTOP management. Study medication was applied once daily for 8 weeks followed by 'as needed' application for an additional 56 weeks. Response was defined as a Physician's Global Assessment (PGA) of 'clear' or 'almost clear'. Results: In 1790 patients (full analysis set), response rates after 8 weeks (primary objective) were significantly higher for TTOP (36·3%) than for non‐TTOP (31·3%, P = 0·0267). Better clinical outcome was accompanied by higher rates of patients feeling well informed about their skin condition, treatment and other factors related to adherence, but the Dermatology Life Quality Index was not statistically different. TTOP patients regarded the structured one‐to‐one conversations with their dermatologist/nurse as the most important element of TTOP. Conclusions: Patients randomized to the TTOP intervention had a better clinical response than patients receiving standard of care. Improved communication between the healthcare provider and patient might be an important element in increasing adherence to topical therapy in psoriasis. Abstract : What's already known about this topic? Adherence rates in chronically ill patients, particularly those with psoriasis, are generally low. Poor adherence is linked to worse clinical outcomes and reduced quality of life, in addition to increased direct and indirect costs. Interventions are needed to improve adherence in patients with psoriasis, which should be multifaceted and tailored to the patient's individual needs so that these interventions are suitable for long‐term use. What does this study add? The Topical Treatment Optimization Programme (TTOP) was designed based on input from experts and patients and comprises structured guidance for one‐to‐one conversations between dermatologist/nurse and patients, patient information materials, telephone/e‐mail helpdesks and treatment reminders. Patients randomized to TTOP had a significantly better clinical outcome than patients receiving standard of care, despite using less study medication. Improved communication between the dermatologist/nurse and patient might be important for increasing adherence to topical therapy in psoriasis. Respond to this article Plain language summary available online